Managing counselors' secondary traumatic stress experiences through self-care - Zakaria, Mohd Zaliridzal; Zakaria, Noor Syamilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
The experience of providing crisis intervention and traumatic stress services among counselors and mental health professionals can develop a form of negative impact within the experiences gained by counselors. According to Figley (1995), the term secondary traumatic stress is defined as a natural consequence resulting from knowing or witnessing a traumatizing event experienced by a significant other. Counseling psychologist or counselors who have been prepared with skills and techniques to provide empathy for their clients and others sometimes fail to provide the need of empathy and self-care for themselves. However, the process of transforming the clients traumatic experience and the nature of caring for others as the ethics of counseling service as a whole comes down to the individual counsellor taking a risk of harming their own self. Wellness perspectives encourages a balance in personal and professional life practices and ensure a holistic personal self-care agenda that may lessen the likelihood of suffering from debilitating symptoms of secondary traumatic-stress.